Evaluasi Akurasi Model Bankometer dalam Memprediksi Financial Distress BPR yang Dicabut Izin Usahanya oleh OJK - Siti Atika Azzahrah; Tri Joko Prasetyo (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to evaluate the accuracy of the Bankometer model in predicting financial distress in 22 rural banks (BPR) and rural bank cooperatives (BPRS) whose business licenses were revoked by the Financial Services Authority (OJK) during the period 2022–2024. The background of this study stems from the increasing number of failed rural banks, which indicates that the conventional ratio-based supervisory approach has not been fully effective in detecting early signs of performance decline. The method used is quantitative descriptive analysis using quarterly financial reports as secondary data and applying the Bankometer S-score calculation to classify the level of bank health. The results show that one year before the revocation of licenses, only a small portion of BPRs were in the distress category, while more than half were classified as very healthy. Two years earlier, the entire sample was even in the super sound category, so the model was unable to provide early signals of deteriorating efficiency and asset quality. These findings indicate that Bankometer is less sensitive to the operational dynamics of rural banks. This study concludes that the model needs to be revised to be more adaptive to the characteristics of microbanking risk